2019
DOI: 10.1186/s12891-019-2537-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 6-week retro or forward walking program on pain, functional disability, quadriceps muscle strength, and performance in individuals with knee osteoarthritis: a randomized controlled trial (retro-walking trial)

Abstract: Background: Previous studies reported the beneficial effects of walking in individual with mild to moderate knee osteoarthritis (OA). The current study aimed to compare the effect of 6-week retro versus forward walking program versus control group on pain, functional disability, quadriceps muscle strength and physical performance in individuals with knee OA. Methods: A three-arm single-blinded, randomized, controlled trial and intention-to-treat analysis was conducted in outpatient physiotherapy department, Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 62 publications
3
49
0
Order By: Relevance
“…Functional ability in performing activities of daily living and sports has been associated with various physio-medical conditions such as body alignment, presence of deformity and pain [38][39][40][41]. In the osteoarthritic knee, pain and deformity are among the main contributing factors to the reduction of functional ability [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Functional ability in performing activities of daily living and sports has been associated with various physio-medical conditions such as body alignment, presence of deformity and pain [38][39][40][41]. In the osteoarthritic knee, pain and deformity are among the main contributing factors to the reduction of functional ability [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Since soothed knee inflammation and joint function recovery are key outcome indicators after rehabilitation training, the main outcomes of this study will be reduced pain perception and joint function recovery in patients. Reduced pain perception can be assessed through patient self-report questionnaires, such as the Numeric Rating Scale for Pain 15 ; joint functional recovery is defined as improved mobility and will be assessed through scales and tests, such as the Timed ‘Up and Go’ test 15 or the Western Ontario and McMaster Universities Osteoarthritis Index. 15 18 …”
Section: Information Sourcesmentioning
confidence: 99%
“… 11–14 Results of a study recommend the use of BW for KOA rehabilitation and adjuvant therapy, because they found that BW can reduce the pain caused by arthritis, optimise joint function and enhance the strength of the quadriceps muscles. 15 However, it has been reported that while walking rehabilitation therapy can improve cardiovascular health in patients with KOA, it does not make any significant effect on reducing pain symptoms. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Backward walking (BW) is a simple and effective method for adjuvant treatment and rehabilitation. [ 10 ] On 1 hand, BW is helpful for improving proprioception, [ 11 , 12 ] muscle strength, [ 13 ] intralimb coordination [ 14 ] and balance. [ 15 ] On the other hand, it can also assess the severity of impairment of coordination and motor ability, and serve as a predictor of falls in the elderly.…”
Section: Introductionmentioning
confidence: 99%